Current Denture Loss in Geriatric Facilities - Miki Endo; Nami Nakayama; Miki Yamada; Yosuke Iijima; Shunsuke Hino; Kiyoko Ariya; Norio Horie; Takahiro Kaneko (Medicines, 2022)
Purpose: Denture loss is still being reported as a problem in geriatric facilities, although losses seem less frequent than in the last decade. However, there have been no reports that have examined recent losses of dentures in detail. The aim of this study was to clarify the actual situation of recent denture loss, together with the denture loss rate in Japan. Materials and methods: This retrospective study investigated the number of cases of denture loss, the denture loss rate for denture wearers, and the details of losses in geriatric facilities during the 1-year period from 1 April 2020 to 31 March 2021. Results: Eleven special elderly nursing homes and four group homes participated in this research. The number of residents from each was 315 and 40 and the number of denture wearers was 165 and 33, respectively (p < 0.001). The loss of dentures was found in one case from a special elderly nursing home and in one case from a group home. The loss rate for denture wearers was 1.01% in total, with 0.61% for special elderly nursing homes and 3.03% for group homes, with no significant differences between the two types of facilities. Conclusion: In geriatric facilities in Japan, the current 1-year denture loss rate for denture wearers was 1.01%. This seems to represent a considerable decrease when compared with the previous report. Further, proper denture management and staff efforts appear to have contributed to a reduction in denture loss against a background of promoting oral healthcare.